2022
DOI: 10.1039/d1dt03823k
|View full text |Cite
|
Sign up to set email alerts
|

A Keggin-type polyoxometalate-based metal–organic complex as a highly efficient heterogeneous catalyst for the selective oxidation of alkylbenzenes

Abstract: A novel type of polyoxometalate-based metal–organic complex was successfully synthesized, which showed good catalytic activity for the oxidation of alkylbenzenes with high conversion, excellent selectivity, and rapid reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The results showed that the conversion of benzyl alcohol decreased significantly after adding carbon radical scavenger butylhydroxytoluene (BHT) and oxygen radical scavenger 2,2,6,6-tetramethylpiperidinyl-1-oxide (TEMPO, 17 % and 24 % respectively), which proved the nature of the radical reaction process. Based on the above observations and literature reports, [34] a possible reaction mechanism was proposed in Figure 6. Initially, TBHP (t-BuOOH) reacted catalytically with the Co(II) site of complex 1 catalyst, resulting in the conversion of t-BuOOH to t-BuO * radical and OH À .…”
Section: Mechanismmentioning
confidence: 72%
“…The results showed that the conversion of benzyl alcohol decreased significantly after adding carbon radical scavenger butylhydroxytoluene (BHT) and oxygen radical scavenger 2,2,6,6-tetramethylpiperidinyl-1-oxide (TEMPO, 17 % and 24 % respectively), which proved the nature of the radical reaction process. Based on the above observations and literature reports, [34] a possible reaction mechanism was proposed in Figure 6. Initially, TBHP (t-BuOOH) reacted catalytically with the Co(II) site of complex 1 catalyst, resulting in the conversion of t-BuOOH to t-BuO * radical and OH À .…”
Section: Mechanismmentioning
confidence: 72%
“…Even though the Ru 3d spectra overlap strongly with the C 1s spectra, the peaks attributed to Ru 3d 5/2 and Ru 3d 3/2 at 282.02 and 286.64 eV, respectively, can be clearly observed, indicating the +3 valence state of Ru element; while the peaks at 284.34 and 288.55 eV originated from C 1s. , The two peaks of Ru 3p (Figure S6c) located at 463.49 and 485.04 eV correspond to Ru 3p 3/2 and Ru 3p 1/2 , respectively, which further confirm the +3 valence state of Ru . As shown in Figure S6d, the peaks at 935.56 and 955.16 eV belong to the binding energy of Cu 2p 3/2 and Cu 2p 1/2 , respectively, confirming the valence state of Cu element as +2. , The Si 2p binding energy at 101.81 eV (Figure S6e), and the W 4f binding energies at 35.26 and 37.63 eV (Figure S6f) show that the Si and W elements have the valence states of +4 and +6, respectively, which is consistent with the literature descriptions. , …”
Section: Resultsmentioning
confidence: 96%
“…46 As shown in Figure S6d, the peaks at 935.56 and 955.16 eV belong to the binding energy of Cu 2p 3/2 and Cu 2p 1/2 , respectively, confirming the valence state of Cu element as +2. 47,48 The Si 2p binding energy at 101.81 eV (Figure S6e), and the W 4f binding energies at 35.26 and 37.63 eV (Figure S6f) show that the Si and W elements have the valence states of +4 and +6, respectively, which is consistent with the literature descriptions. 49,50 Optical and Photoelectrochemical Properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The results show that catalyst 1 can achieve a high selectivity for the majority of alkylbenzenes. As shown in Table , entries 1, 2, 3, and 4, it is worth noting that the electronic effect of substituents influences the catalytic effect more or less . Notably, catalyst 1 shows excellent catalytic performance for the oxidation of fluorene to the corresponding ketone with 99% conversion and 99% selectivity (Table , entry 5).…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Table 1, entries 1, 2, 3, and 4, it is worth noting that the electronic effect of substituents influences the catalytic effect more or less. 55 Notably, catalyst 1 shows excellent catalytic performance for the oxidation of fluorene to the corresponding ketone with 99% conversion and 99% selectivity (Table 1, entry 5). Moreover, tetralin, 4-phenylpyridine, and diphenylmethane derivatives are converted into corresponding ketones with conversion and selectivity of 86.3 and 85.6, 86.7 and 99.0, and 86.6 and 94.5%, respectively, under the optimal conditions (Table 1, entries 6, 7, and 8).…”
Section: ■ Introductionmentioning
confidence: 99%